Jet flipping and scouring characteristics by 2-D wall jets - Er, Jenn Wei. (2013)
In this project, the result of an experimental investigation on scour of non-cohesive and uniform sediment beds downstream of a sluice gate, due to a submerged two-dimensional wall jets issuing from a sluice opening were presented. All the experiments were conducted under high flow submergence with or without an apron. The jet issued from the sluice gate and impinging on an erodible bed can produce two very different flow patterns, depending on the experimental conditions. The observations and characteristics of the sediment bed downstream of the sluice gate during the scouring process was being described and explained in this report.